Industrial Model of Defense Industry Organizations Development - V. V. Dvoretskaya (Учёт. Анализ. Аудит)
At present, Russian industry is characterized by a general slowdown in the growth rate of the economy against the backdrop of the growth of the state defense order. The transition to a modern innovative business model of defense industry organizations becomes an important task. However, traditional approaches to solving the problem of financing innovation activities carried out within the framework of the state defense order are not always applicable. During the sanctions period, the state is not in a position to allocate significant resources for research and development with the aim of turning them into innovative products. There are problems with attracting private investors, although starting investments in the creation of innovative products are a critical factor in their creation and further development. However, the investment attractiveness of the defense industry enterprises is rather low, therefore it is necessary to consider the various forms and methods of financing, as well as the possibility of attracting sources of financial resources that are unconventional for the enterprises of the defense industry. To create a significant interest of private investors, you can offer to use not only tax incentives, but also the right to use the results of development. An additional motivating incentive may turn out the changes in tax legislation that provide a more convenient and quick way for the transition of defense enterprises to a modern industrial business model. The examples of such changes may include the establishment of various tax and legal conditions for procurement for military and special-purpose products and general (civil) use, decreasing the property tax through disposal of non-core and unused assets or the opportunity to use the savings of resources on the project, when reinvesting them into new research or acquiring high-tech equipment without additional taxation.